Segmented aliphatic polycarbonate capable of introducing unsaturated functional group and preparation method thereof

By introducing the polyester domain into the large molecular weight aliphatic polycarbonate, the formation of segmented aliphatic polycarbonate is solved, and the problem of limited performance adjustment range of polyester materials is achieved is significantly improved.

CN119638971AActive Publication Date: 2025-03-18CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411827583.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The single composition structure of existing polyester materials leads to a limited range of material performance adjustment and is difficult to apply to a wider range of application scenarios, especially in replacing polyolefin materials.

Method used

By introducing the polyester domain on the basis of large molecular weight aliphatic polycarbonate for segmentation, a segmented aliphatic polycarbonate is formed, and segmented polymerization is performed using heterogeneous catalyst surface catalyst chain transfer method to accurately regulate the polymer structure.

Benefits of technology

The segmented structure of the polymer chain is realized, which significantly regulates the mechanical properties, including improving elongation of break and tensile strength, and is suitable for a wider range of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638971A_ABST
    Figure CN119638971A_ABST
Patent Text Reader

Abstract

The invention provides segmented aliphatic polycarbonate capable of introducing an unsaturated functional group. The segmented aliphatic polycarbonate has a structure as shown in a formula I, r1 is selected from substituent groups on side chains after ring-opening copolymerization of epoxy compounds as shown in formulas 101-108 and dioxo ring carbon or cyclic anhydride; the structure of R2 is formed after ring opening of cyclic anhydride and an epoxy compound; n and m are both non-zero natural numbers. According to the polymer, a polyester domain is introduced on the basis of high-molecular-weight aliphatic polycarbonate for segmentation, and a polymer chain is converted into a sectional structure, so that the mechanical property of the polymer can be greatly adjusted. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymers, and in particular relates to a segmented aliphatic polycarbonate capable of introducing unsaturated functional groups and a preparation method thereof. Background Art

[0002] The development and use of degradable polymer materials to replace traditional polyolefin materials is a hot topic in today's scientific research and social fields. The large-scale application of degradable polymer materials will help alleviate the "white pollution" problem and build a sustainable society. Polyester materials represented by polylactic acid and polycaprolactone can be biodegraded in the natural environment, and the materials have excellent mechanical and thermodynamic properties. They have been widely used in disposable tableware, packaging materials and biological tissue engineering. However, the composition structure of these polyester materials is single, resulting in a small adjustment range of material properties, and cannot be used in a wider range of application scenarios to replace polyolefin materials. Carbon dioxide-based polycarbonate materials can be prepared by copolymerization of epoxides and CO2 as raw materials. This type of material is also biodegradable, and has the advantages of rich monomer substitution structure, wide sources, and "greenhouse gas" CO2 as the source of C1, which has also attracted the attention of scientific researchers.

[0003] The synthesis of copolymers with both epoxide / CO2 copolymer segments and polyester segments can combine the advantages of both types of materials to achieve the purpose of improving material performance and expanding application scenarios. However, the activity of different monomers varies greatly, and existing catalysts rarely can efficiently copolymerize three monomers at the same time. Affected by the difference in the competitive polymerization rate between different monomers, the copolymerization reaction of the three monomers under the action of a homogeneous catalyst usually produces block copolymers, gradient copolymers or random copolymers. Correspondingly, periodic / segmented copolymers are difficult to synthesize, and there are almost no related reports. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a segmented aliphatic polycarbonate that can introduce unsaturated functional groups and a preparation method thereof. The polymer is segmented by introducing a polyester domain on the basis of a large molecular weight aliphatic polycarbonate, converting the polymer chain into a segmented structure, which can greatly adjust the mechanical properties of the polymer.

[0005] The present invention provides a segmented aliphatic polycarbonate capable of introducing unsaturated functional groups, having a structure of formula I:

[0006]

[0007] The R1 is selected from the substituents on the side chain after the ring-opening copolymerization of the epoxy compound and the dioxycarbon or cyclic anhydride as shown in the following formulas 101 to 108:

[0008]

[0009] The structure of R2 is a structure formed by ring opening of a cyclic anhydride and an epoxy compound;

[0010] Both n and m are non-zero natural numbers.

[0011] Preferably, the cyclic acid anhydride is selected from any one of Compound 1 to Compound 26:

[0012]

[0013]

[0014] Preferably, the segmented aliphatic polycarbonate has the structures of Formula I-1 to Formula I-6:

[0015] Preferably, a single anhydride-epoxy unit in the segmented aliphatic polycarbonate is the smallest structural domain;

[0016] The minimum domain content is 1 to 20 wt%.

[0017] Preferably, the glass transition temperature of the segmented aliphatic polycarbonate is 32-42°C.

[0018] The present invention provides a method for preparing the segmented aliphatic polycarbonate capable of introducing unsaturated functional groups as described in the above technical solution, comprising the following steps:

[0019] An epoxy compound, a cyclic anhydride monomer, CO2, a solvent and a heterogeneous catalyst surface catalyst are mixed and polymerized to obtain a segmented aliphatic polycarbonate having a structure of formula I.

[0020] Preferably, the heterogeneous catalyst is selected from one or more of zinc glutarate, metal-supported zinc glutarate and double metal cyanide;

[0021] The molar mass ratio of the heterogeneous catalyst to the epoxy compound is 1:200-1000.

[0022] Preferably, the pressure of the CO2 is 0.5-3.5 MPa.

[0023] Preferably, the polymerization reaction temperature is 50 to 120° C., and the polymerization reaction time is 6 to 48 hours.

[0024] Preferably, the molar ratio of the anhydride monomer to the epoxy compound is 0.025 to 0.5:1.

[0025] The present invention provides a segmented aliphatic polycarbonate capable of introducing unsaturated functional groups, having a structure of formula I. The polymer is segmented by introducing a polyester domain on the basis of a large molecular weight aliphatic polycarbonate, converting the polymer chain into a segmented structure, and being able to greatly adjust the mechanical properties of the polymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the polycarbonate prepared in Example 1 of the present invention;

[0027] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of the polycarbonate prepared in Example 4 of the present invention;

[0028] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of the polycarbonate prepared in Example 6 of the present invention;

[0029] Figure 4 This is the hydrogen nuclear magnetic resonance spectrum of the polycarbonate prepared in Example 7 of the present invention;

[0030] Figure 5 This is the hydrogen nuclear magnetic resonance spectrum of the polycarbonate prepared in Example 8 of the present invention;

[0031] Figure 6 This is the hydrogen nuclear magnetic resonance spectrum of the polycarbonate prepared in Example 9 of the present invention. DETAILED DESCRIPTION

[0032] The present invention provides a segmented aliphatic polycarbonate capable of introducing unsaturated functional groups, having a structure of formula I:

[0033]

[0034] The R1 is selected from the substituents on the side chain after the ring-opening copolymerization of the epoxy compound and the dioxycarbon or cyclic anhydride as shown in the following formulas 101 to 108:

[0035]

[0036] The structure of R2 is a structure formed by ring opening of a cyclic anhydride and an epoxy compound;

[0037] Both n and m are non-zero natural numbers.

[0038] The present invention uses a theoretical minimum structural domain (single anhydride-epoxy unit) to precisely regulate the polymer structure, and can significantly improve the elongation at break of the aliphatic polycarbonate material when a small amount of anhydride monomer is introduced.

[0039] The cyclic acid anhydride used to form the R1 or R2 substituent in the present invention is selected from any one of Compounds 1 to 26:

[0040]

[0041]

[0042] The segmented aliphatic polycarbonate described in the present invention has the structures of Formula I-1 to Formula I-6:

[0043]

[0044]

[0045] The single anhydride-epoxy unit in the segmented aliphatic polycarbonate provided by the present invention is the minimum domain; the minimum domain content is 1-20wt%, the relative molecular mass of the corresponding polymer is 100-600kDa, n=5-30, m=300-1800; in a specific embodiment, the minimum domain content is 7%, 1%, 4%, 9%, 6% or 3%. The glass transition temperature of the segmented aliphatic polycarbonate is 32-42°C; the maximum tensile strength is 4-36MPa, the elongation at break is 10-1100%, and a 1% change in the domain content of the same type of material can achieve an 80% change in the elongation at break.

[0046] The present invention provides a method for preparing the segmented aliphatic polycarbonate capable of introducing unsaturated functional groups as described in the above technical solution, comprising the following steps:

[0047] An epoxy compound, a cyclic anhydride monomer, CO2, a solvent and a heterogeneous catalyst surface catalyst are mixed and polymerized to obtain a segmented aliphatic polycarbonate having a structure of formula I.

[0048] The present invention preferably carries out the above reaction in a high pressure reactor. The present invention uses a heterogeneous catalyst surface catalyst chain transfer method to segment the polymer. In this process, due to the difference in monomer activity, the anhydride cannot be inserted continuously, forming a single anhydride-epoxy unit as the minimum structural domain.

[0049] The heterogeneous catalyst used in the present invention is selected from one or more of zinc glutarate (ZnGA), metal-supported zinc glutarate (ZnGA / MY, M is a metal ion, Y is an anion) and double metal cyanide (DMC); in a specific embodiment, the heterogeneous catalyst is a ZnGA / NaCl catalyst; the molar ratio of the heterogeneous catalyst to the epoxy compound is 1:200-1000; in a specific embodiment, the molar ratio of the heterogeneous catalyst to the epoxy compound is 1:500. The pressure of CO2 used in the present invention is 0.5-3.5MPa; in a specific embodiment, the pressure of CO2 is 2MPa. The solvent in the present invention is selected from one or more of toluene, xylene, tetrahydrofuran, dichloromethane, dichloroethane, n-hexane and 1,4-dioxane.

[0050] The epoxy compound described in the present invention is consistent with the epoxy compound type range shown in Formula 101 to Formula 108 above; the selection range of the cyclic anhydride monomer is consistent with the cyclic anhydride shown in Compound 1 to Compound 26 above. The molar ratio of the cyclic anhydride to the epoxy compound is 0.025 to 0.5:1; in a specific embodiment, the molar ratio of the cyclic anhydride to the epoxy compound is 1:10, 1:20, 1:40 or 1:5. In a specific embodiment, the epoxy compound is selected from propylene oxide or styrene oxide; the cyclic anhydride is selected from 1,2-cyclohexanedicarboxylic anhydride, phthalic anhydride, maleic anhydride or succinic anhydride.

[0051] The polymerization temperature of the present invention is 50-120° C., and the polymerization time is 6-48 hours. In a specific embodiment, the polymerization temperature is 70° C., and the polymerization time is 24 hours.

[0052] In order to further illustrate the present invention, a segmented aliphatic polycarbonate capable of introducing unsaturated functional groups and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0053] Example 1

[0054] Propylene oxide (29.7 g) was added to the autoclave, and a ZnGA / NaCl catalyst (0.2 g) with a molar ratio of 1:500 to propylene oxide was added, and phthalic anhydride (7.58 g) with a molar ratio of 1:10 to propylene oxide was added, and 2 MPa of carbon dioxide was charged, and the temperature was raised to 70° C. and reacted for 24 hours to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain a material having the following structure:

[0055]

[0056] Sampling 1H NMR test showed that the minimum domain (phthalic anhydride-epoxy) content was 7%. After sample preparation, the thermodynamic properties were tested, with a glass transition temperature of 39° C., a maximum tensile strength of 35.0 MPa, and an elongation at break of 11%.

[0057] Example 2

[0058] Propylene oxide (29.7 g) was added to the autoclave, and a ZnGA / NaCl catalyst (0.2 g) with a molar ratio of 1:500 to propylene oxide was added, and phthalic anhydride (3.89 g) with a molar ratio of 1:20 to propylene oxide was added, and 2 MPa of carbon dioxide was charged, and the temperature was raised to 70° C. and reacted for 24 hours to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) to precipitate, filtered, and the filter cake was collected and dried to obtain a material having the following structure:

[0059]

[0060] Sampling 1 H NMR test showed that the minimum domain (phthalic anhydride-epoxy) content was 3%. After sample preparation, the thermodynamic properties were tested, with a glass transition temperature of 39°C, a maximum tensile strength of 9 MPa, and an elongation at break of 320%.

[0061] Example 3

[0062] Propylene oxide (29.7 g) was added to the autoclave, and a ZnGA / NaCl catalyst (0.2 g) with a molar ratio of 1:500 to propylene oxide was added, and phthalic anhydride (1.95 g) with a molar ratio of 1:40 to propylene oxide was added, and 2 MPa of carbon dioxide was charged, and the temperature was raised to 70° C. and reacted for 24 hours to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain a material having the following structure:

[0063]

[0064] Sampling 1 H NMR test showed that the minimum domain (phthalic anhydride-epoxy) content was 1%. After sample preparation, the thermodynamic properties were tested, with a glass transition temperature of 39° C., a maximum tensile strength of 36 MPa, and an elongation at break of 40%.

[0065] Example 4

[0066] Propylene oxide (29.7 g) was added to the autoclave, and a ZnGA / NaCl catalyst (0.2 g) with a molar ratio of 1:500 to propylene oxide was added, and a succinic anhydride (3.85 g) with a molar ratio of 1:10 to propylene oxide was added, and 2 MPa of carbon dioxide was charged, and the temperature was raised to 70° C. and reacted for 24 hours to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain a material having the following structure:

[0067]

[0068] Sampling 1 H NMR test showed that the minimum domain (succinic anhydride-epoxy) content was 4%. After sample preparation, the thermodynamic properties were tested, with a glass transition temperature of 36°C, a maximum tensile strength of 20 MPa, and an elongation at break of 410%.

[0069] Example 5

[0070] Propylene oxide (29.7 g) was added to the autoclave, and a ZnGA / NaCl catalyst (0.2 g) with a molar ratio of 1:500 to propylene oxide was added, and a succinic anhydride (7.49 g) with a molar ratio of 1:5 to propylene oxide was added, and 2 MPa of carbon dioxide was charged, and the temperature was raised to 70° C. and reacted for 24 hours to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain a material having the following structure:

[0071]

[0072] Sampling 1 H NMR test showed that the minimum domain (succinic anhydride-epoxy) content was 7%. After sample preparation, the thermodynamic properties were tested, with a glass transition temperature of 32°C, a maximum tensile strength of 8 MPa, and an elongation at break of 1100%.

[0073] Example 6

[0074] Propylene oxide (29.7 g) was added to the autoclave, and a ZnGA / NaCl catalyst (0.2 g) with a molar ratio of 1:500 to propylene oxide was added, and maleic anhydride (3.80 g) with a molar ratio of 1:10 to propylene oxide was added, and 2 MPa of carbon dioxide was charged, and the temperature was raised to 70° C. and reacted for 24 hours to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain a material having the following structure:

[0075]

[0076] Sampling 1H NMR test showed that the minimum domain (maleic anhydride-epoxy) content was 8%. After sample preparation, the thermodynamic properties were tested, with a glass transition temperature of 39° C., a maximum tensile strength of 20 MPa, and an elongation at break of 400%.

[0077] The sample can then be cross-linked by Michael addition reaction at a ratio of sample: ethanedithiol: triethylamine = 15:1:1.

[0078] Example 7

[0079] Propylene oxide (29.7 g) was added to the autoclave, and a ZnGA / NaCl catalyst (0.2 g) with a molar ratio of 1:500 to propylene oxide was added, and 1,2-cyclohexanedicarboxylic anhydride (7.58 g) with a molar ratio of 1:10 to propylene oxide was added, and 2 MPa of carbon dioxide was charged, and the temperature was raised to 70° C. and reacted for 24 hours to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain a material having the following structure:

[0080]

[0081] Sampling 1 H NMR test showed that the minimum domain (1,2-cyclohexanedicarboxylic anhydride-epoxy) content was 3%. After sample preparation, the thermodynamic properties were tested, with a glass transition temperature of 39°C, a maximum tensile strength of 33 MPa, and an elongation at break of 400%.

[0082] Example 8

[0083] Styrene oxide (61.4 g) was added to the autoclave, and a ZnGA / NaCl catalyst (0.2 g) with a molar ratio of 1:500 to propylene oxide was added, and phthalic anhydride (7.58 g) with a molar ratio of 1:10 to propylene oxide was added, and 2 MPa of carbon dioxide was charged, and the temperature was raised to 70° C. and reacted for 24 hours to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain a material having the following structure:

[0084]

[0085] Sampling 1 H NMR test showed that the minimum domain (phthalic anhydride-epoxy) content was 7%. After sample preparation, the thermodynamic properties were tested, with a glass transition temperature of 49°C, a maximum tensile strength of 56.0 MPa, and an elongation at break of 6%.

[0086] Example 9

[0087] Furfuryl glycidyl ether (78.8 g) was added to the autoclave, ZnGA / NaCl catalyst (0.2 g) was added in a molar ratio of 1:500 to propylene oxide, phthalic anhydride (7.58 g) was added in a molar ratio of 1:10 to propylene oxide, and 2 MPa of carbon dioxide was charged, the temperature was raised to 70°C, and the reaction was carried out for 24 hours to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain a material having the following structure:

[0088]

[0089] Sampling 1 H NMR test showed that the minimum domain (phthalic anhydride-epoxy) content was 6%. After sample preparation, the thermodynamic properties were tested, with a glass transition temperature of 32° C., a maximum tensile strength of 16.0 MPa, and an elongation at break of 60%.

[0090] As can be seen from the above examples, the present invention provides a segmented aliphatic polycarbonate capable of introducing unsaturated functional groups, having a structure of Formula I. The polymer is segmented by introducing a polyester domain on the basis of a large molecular weight aliphatic polycarbonate, converting the polymer chain into a segmented structure, and can greatly adjust the mechanical properties of the polymer.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A segmented aliphatic polycarbonate capable of introducing unsaturated functional groups, having a structure of formula I: The R1 is selected from the substituents on the side chain after the ring-opening copolymerization of the epoxy compound and the dioxycarbon or cyclic anhydride as shown in Formulas 101 to 108: The structure of R2 is a structure formed by ring opening of a cyclic anhydride and an epoxy compound; Both n and m are non-zero natural numbers.

2. The segmented aliphatic polycarbonate capable of introducing unsaturated functional groups according to claim 1, characterized in that: The cyclic acid anhydride is selected from any one of Compound 1 to Compound 26:

3. The segmented aliphatic polycarbonate capable of introducing unsaturated functional groups according to claim 1, characterized in that: Segmented aliphatic polycarbonate has the structures of Formula I-1 to Formula I-6:

4. The segmented aliphatic polycarbonate capable of introducing unsaturated functional groups according to claim 1, characterized in that: A single anhydride-epoxy unit in the segmented aliphatic polycarbonate is the smallest structural domain; The minimum domain content is 1 to 20 wt%.

5. The segmented aliphatic polycarbonate capable of introducing unsaturated functional groups according to claim 1, characterized in that: The glass transition temperature of the segmented aliphatic polycarbonate is 32-42°C.

6. A method for preparing the segmented aliphatic polycarbonate capable of introducing unsaturated functional groups as claimed in claim 1, comprising the following steps: An epoxy compound, a cyclic anhydride monomer, CO2, a solvent and a heterogeneous catalyst surface catalyst are mixed and polymerized to obtain a segmented aliphatic polycarbonate having a structure of formula I.

7. The preparation method according to claim 6, characterized in that: The heterogeneous catalyst is selected from one or more of zinc glutarate, metal-supported zinc glutarate and double metal cyanide; The molar mass ratio of the heterogeneous catalyst to the epoxy compound is 1:200-1000.

8. The preparation method according to claim 6, characterized in that: The pressure of the CO2 is 0.5-3.5 MPa.

9. The preparation method according to claim 6, characterized in that: The polymerization reaction temperature is 50-120° C., and the polymerization reaction time is 6-48 hours.

10. The preparation method according to claim 6, characterized in that: The molar ratio of the anhydride monomer to the epoxy compound is 0.025 to 0.5:1.

Citation Information

Patent Citations

  • Ternary copolymer polycarbonate foam material

    CN102504231A

  • Process for preparing polycarbonates by polymerization of five-membered-ring cyclic carbonates

    CN105358604A

  • Process for preparing degradable protecting film resisting against water and oil

    CN1328098A

  • Terpolymerization of carbon dioxide, epoxide and cyclic anhydride

    KR1020150106642A